Syndrome in Question - Han MA; Meilan Chen; Juan Li; Ying Li; Shu Qiu (Sociedade Brasileira de Dermatologia, 2015)
Immunoglobulin light chain amyloidosis is the most common acquired systemic amyloidosis. Its presentation is often insidious and progressive, which may delay diagnosis. The authors describe a rare case of immunoglobulin light chain amyloidosis in a 34-year-old man with scleroderma-like manifestation substantiated by multifarious laboratory investigations and the histopathologic feature of involved skin lesions stained with Congo red and crystal violet. This helps to maintain a high clinical suspicion of the disease when confronting similar skin presentation.